INTERNALISASI NILAI-NILAI KEAGAMAAN MELALUI KEGIATAN PEMBIASAAN PERILAKU RELIGI (P2R) DI SEKOLAH DASAR NEGERI JERANG BARAT KOTA CILEGON - Mustika, Rika; Ngulwiyah, Istinganatul; M, Taufik; Setiawan, Sigit (Jurnal Pendidikan Dasar, 2024)
This research aims to analyze and describe the process of internalizing religious values through religious behavior habituation activities (P2R), supporting capacity and challenges and religious behavior that is formed in grade 6 students at the West Jerang State Elementary School, Cilegon City. The research method uses a qualitative approach with descriptive methods. Research data sources include school principals, 6th grade teachers and islamic religious education subject teachers. Data collection techiques use interviews, observation and documentation. Data analysis using qualitative data analysis includes data collection, data reduction, data prsentation and drawing conclusions. The results of research on the aspect of the process of internalizing religious values through P2R activities have been carried out well, as evidenced by the students memorizing asmaul husna with a total 20 asmaul husna, memorizing short letters in juz amma from surat al-fath to al-ashr, memorizing the prophets prayers, memorizing general prayers such as prayers for parents, prayers for the afterlife, can carry out ablution and practice sunnah dhuha prayers in congregation. In the aspect of carrying capacity in implementing P2R activities, the facilities and infrastructure are edequate, while the challenges are related to students motivation which fluctuates due to feeling bored, so it requires improvements in implementing P2R activities. In the aspect of religious behavior that is formed from the implementation of P2R activities, both aspect of faith values, woship values and moral values have begun to be formed and carried out by students in their activities while in the school environment.